2005
DOI: 10.1097/01.aud.0000188185.78217.c5
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition and Comfort Using Hearing Instruments with Adaptive Directional Characteristics in Asymmetric Listening Conditions

Abstract: It is concluded that bilateral hearing instruments with adaptive directional microphones confer benefits in terms of speech recognition in noise and sound quality. Independence of the two adaptive control systems does not appear to cause untoward effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
(3 reference statements)
1
14
0
Order By: Relevance
“…The amount of reduction, however, decreased as the number of noise sources increased. These findings were consistent with previous studies showing that adaptive directional microphones provided better directional benefits than fixed directional microphones with a few fixed or moving noise sources (Kompis and Dillier, 2001;Ricketts and Henry, 2002;Mackenzie and Lutman, 2005;Blamey et al, 2006;Maj et al, 2004Maj et al, , 2006.…”
Section: Discussionsupporting
confidence: 94%
“…The amount of reduction, however, decreased as the number of noise sources increased. These findings were consistent with previous studies showing that adaptive directional microphones provided better directional benefits than fixed directional microphones with a few fixed or moving noise sources (Kompis and Dillier, 2001;Ricketts and Henry, 2002;Mackenzie and Lutman, 2005;Blamey et al, 2006;Maj et al, 2004Maj et al, , 2006.…”
Section: Discussionsupporting
confidence: 94%
“…This situation was investigated by Mackenzie and Lutman: The authors found that although the adaptive systems worked independently, there were no detrimental effects, as measured by sentence recognitions scores in noise or quality ratings [20]. In fact, bilateral use of both the adaptive and the fixed system was consistently superior to the omnidirectional settings.…”
Section: Introductionmentioning
confidence: 99%
“…These microphones, by design, can reduce the level of sounds coming from the sides and back. In situations where the desired signal is in front and noise sources are located at the sides or back, directional microphones can enhance speech recognition performance and improve perceived sound quality for hearing aid and cochlear implant users ͑Hawkins and Yacullo, 1984; Killion et al, 1998;Ricketts and Dhar, 1999;Kuhnel et al, 2001;Ricketts and Henry, 2002;Bentler et al, 2004;Walden et al, 2004;Amlani et al, 2006;Mackenzie and Lutman, 2005;Valente et al, 2006;van Hoesel and Clark, 1995;Wouters et al, 1999;Blamey et al, 2006;Chung et al, 2006;Spriet et al, 2007;van der Beek et al, 2007͒. It is possible that they can produce similar advantages for HPD users.…”
Section: Introductionmentioning
confidence: 94%